Sraffa, Hume, and Wittgenstein’s Lectures On Belief - Lucia Morra (Nordic Wittgenstein Review, 2019)
As the recent edition of the Wittgenstein’s Whewell’s Court Lectures shows, Wittgenstein mentioned Hume several times in the series of lectures on belief. Towards the end of the Thirties, in fact, he came across Hume’s Abstract of the Treatise, a pamphlet that Piero Sraffa and John Maynard Keynes had ‘discovered’ at the end of 1933, re-edited in 1937 and finally published in March 1938 – Sraffa, with whom Wittgenstein had an intense intercourse in 1938-1941, donated him a copy. A lexical analysis of excerpts of Wittgenstein’s ET 1940 lectures strongly suggests that he read the Abstract in March-May 1940, and shows that some of the issues he discussed in his lectures at that time revolve around the peculiar definition that Hume gave in that text of the feeling of belief.